Art Therapy and Political Violence with Art, Without Illusion (Routledge, 2005)
The impact of political violence, war, civil war and acts of terrorism on the individuals involved can be extensive. Art therapy can provide an effective means of expressing the resulting experiences of fear, loss, separation, instability and disruption. Art Therapy and Political Violence brings together contributions from all over the world and from diverse theoretical backgrounds. With contributions from Northern Ireland, Kosovo, Israel and South Africa, the book includes numerous clinical examples to vividly illustrate the main issues affecting art therapy. The practical issues involved are also discussed, including subjects such as the importance of working with both the internal and external worlds of the individual and sensitivity to cultural issues. Art therapists, psychotherapists and other mental health professionals, particularly those working in the context of political violence or in countries of refuge, will find the experiences recounted in Art Therapy and Political Violence thought-provoking and will welcome the wealth of practical information provided.